The Long-term Effectiveness of the Automatic Position-Adaptive System in Spinal Cord Stimulation: A Retrospective Comparative Study with a Two-Year Follow-up. Issue 10 (13th March 2020) - Kim, Eun kyoung; Lee, Chang-soon; Yoo, Yongjae; Park, Jin-Woo; Kim, Jung Soo; Kim, Youngwon; Moon, Jee Youn; Kim, Yong-Chul
Abstract: Objective: To compare the nonadaptive manual system with the position-adaptive system in subjects with permanent spinal cord stimulator (SCS) implantation over a two-year follow-up period. Design: Retrospective study. Setting: Tertiary university-based national hospital. Subjects: Patients who underwent permanent SCS implantation procedures. Methods: Patients were divided into an adaptive group and a nonadaptive group according to the type of implanted SCS device. The primary outcome was the change (%) in pain intensity from baseline between the adaptive and nonadaptive groups at 24 months after SCS implantation. The secondary outcomes were comparisons of detailed clinical variables such as the scores of patient pain and satisfaction during the two-year follow-up after SCS therapy. Further, the number of subjects with SCS removal or revision within two years after SCS implantation was investigated. Results: Of 187 patients with permanent SCS implantation, 85 in the nonadaptive group and 64 in the position-adaptive group were finally analyzed. The reduction in pain intensity at 24 months was higher in the adaptive group (−38.6%) than in the nonadaptive group (−30.8%, P  = 0.05). Similarly, patient satisfaction with the SCS treatment at 24 months was superior in the adaptive group than in the nonadaptive group (85.7% vs 67.5% were satisfied in each group, respectively, P  = 0.024). During the two years, 5.3% of patients (N = 10) underwent SCS removal and 7.0% (N = 13) underwent revision procedures. Conclusions: There was a trend of a sustained reduction in pain intensity as well as improvement in patient satisfaction at two-year follow-up in the position-adaptive system, suggesting long-term benefit over the nonadaptive manual system during SCS treatment.